Nutrition Therapy on Cutaneous Lymphoma Patient with Anemia and Hypoalbuminemia: A Case Report - Tyas, Fitri; As'ad, Suryani; Safitri, Asrini; Bamahry, Aryanti (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Nutrition is a part of cancer management during therapy, recovery, remission, and recurrence prevention. Malnutrition and cachexia often occur in cancer patients and influence morbidity, mortality, and quality of life, especially in the advanced stage of malignancy. We reported a case of cutaneous lymphoma with anemia and hypoalbuminemia in the terminal condition. This case report focuses on nutritional therapy and palliative care on nutrition. We reported a case of a 40-year-old-man with Cutaneous Lymphoma (CL) and moderate protein-energy malnutrition that was developed to severe protein-energy malnutrition due to difficulty in dietary access. He had an eating problem because of multiple tumors and ulcers on his mouth. We provided access for parenteral nutrition from Central Venous Catheter (CVC) and orogastric tube (OGT) for enteral feeding. Even though the dietary target was never accomplished, there was a slight recovery on hypoalbuminemia and renal function during hospitalization. This case showed a considerable challenge in nutritional therapy due to limited dietary access. Since death was inevitable, we have tried different dietary access to provide adequate intake.